Translating Scientific Articles to the Non-scientific Public Using the Wikipedia Encyclopedia - Leuthold, Julien; Gilli, Adrian (Frontiers in Education, 2019)
The multilingual, web-based Wikipedia free Encyclopedia is used worldwide by people from different audience. It is openly editable, allowing quick updates. We used these properties as an educational tool in University classrooms, where students’ assignment was to rephrase scientific articles for the public. We share here our teaching experience with an Earth Sciences class, based on class assessments and students evaluations. During the 2017 Fall semester, a 1 ECTS MSc level reading seminar on the broad topic of Heat and Mass Transfers in Magmatology was taught for 6 weeks at ETH Zürich. Three first semester and six third semester M.Sc. students have attended the course. All students had a B.Sc. degree in Earth Sciences, among which seven had their main specialisation in Mineralogy and Geochemistry and two had their major in Geophysics. By groups of two, students have read a scientific article, presented it orally to classmates and answered questions from their peers. During the last two classes, students have edited and created Wikipedia Encyclopedia pages in relation to their article’s topic. Students really enjoyed creating a Wikipedia page, even if they didn’t use it before or didn’t trust the Wikipedia content. They had little experience with communication to a non-scientific audience and considered this exercise was challenging. Evaluations show that writing about a scientific paper in a Wikipedia page is a less efficient learning technique than reading a scientific article, presenting it orally or listening to such a presentation. However, it certainly contributes to better memorise important information, it is an efficient way to practice writing and public and scientific communication skills and it encourages students to work collaboratively on real-time projects. The teachers can use those combined effects as a multi-channel learning technique. It is also highly motivating for the students and the teacher to have a class exercise using modern media techniques with the potential to reach a wide international community. With this article, we wish to encourage colleagues to teach students how to communicate science, to scientific peers and to the non-scientific public. This promotes high-quality education and helps reducing inequality, two sustainable development global goals.